Factors influencing the residency of bettongs using one‐way gates to exit a fenced reserve. (22nd July 2020) - Moyses, Jessie; Hradsky, Bronwyn; Tuft, Katherine; Moseby, Katherine; Golding, Nicholas; Wintle, Brendan
Abstract: Understanding the conditions under which small native Australian mammals can persist in the presence of introduced predators remains a key challenge to conservation ecologists. Bettong‐specific one‐way gates were used at a predator‐free reserve in South Australia to allow the burrowing bettong ( Bettongia lesueur ) – a small potoroid, listed as 'vulnerable' nationally – to disperse out of the reserve. We conducted a field experiment to explore the conditions affecting residence time of bettongs that left the reserve. We monitored bettong and mammalian predator activity outside the fence using track surveys across 18 sites over two seasons. We examined the effect of supplementary feeding as a strategy for increasing residence time, as well as the influence of predator presence and habitat quality, using linear mixed models. Bettong activity was positively associated with supplementary feeding, midstorey vegetation cover and shelter availability. After gates were closed, bettong activity near gates declined to almost zero the following weeks, likely either due to death from predation or due to movement away from the sites. To a small extent, mammalian predators were more likely to be present at sites with high bettong activity. Further research on conditions to support persistence of burrowing bettongs and other small mammals, including understanding minimum necessary predator control effort, is required before successful establishment of populations outside of fences can occur.